2011
DOI: 10.1016/j.niox.2010.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between nitric oxide and hypoxia-inducible factor signaling pathways in inflammatory disease

Abstract: Induction and activation of nitric oxide (NO) synthases (NOS) and excessive production of NO are common features of almost all diseases associated with infection and acute or chronic inflammation, although the contribution of NO to the pathophysiology of these diseases is highly multifactorial and often still a matter of controversy. Because of its direct impact on tissue oxygenation and cellular oxygen (O 2 ) consumption and redistribution, the ability of NO to regulate various aspects of hypoxia-induced sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 179 publications
3
91
0
2
Order By: Relevance
“…It is important to notice that HIF-1␣ overactivation can be stimulated by many other mechanisms independently of oxygen levels, such as oxidative stress and proinflammatory factors (13,20,22,47,48,55,62). These oxygenindependent mechanisms are well known to participate in chronic kidney damage in a variety of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to notice that HIF-1␣ overactivation can be stimulated by many other mechanisms independently of oxygen levels, such as oxidative stress and proinflammatory factors (13,20,22,47,48,55,62). These oxygenindependent mechanisms are well known to participate in chronic kidney damage in a variety of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, NO is a nitrogen free radical and can act as a cytotoxic agent in pathological processes, particularly in inflammatory disorders. [12][13][14] NO is mainly produced by microglia and macrophages from L-arginine by a family of enzymes known as NO synthases (NOS). There are three distinct isoforms of NOS, and their distribution is largely related to their respective functions.…”
mentioning
confidence: 99%
“…Nitric oxide production, a hallmark of inflammation, appears to have an important role in hypoxic signaling and hypoxia inducible factor induction (Olson and van der Vliet 2011) and a recent review concluded that increased nitric oxide synthesis is associated with an improved response to hypoxia (Beall et al. 2012).…”
Section: Discussionmentioning
confidence: 99%